2021
DOI: 10.1029/2021ea001894
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Jet Noise Similarity Spectra to Volcano Infrasound Data

Abstract: The eruption of gas and other material by volcanoes perturbs the surrounding air and generates pressure waves, including acoustic waves. Due to the large dimensions of volcanoes and volcanic events, the associated sounds are usually in a low-frequency band below human audibility, called infrasound. The physical source process generating the infrasonic waves can vary for different eruptions or even within an eruption. An often used analogy was introduced by Woulff and McGetchin (1976) and describes the volcano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Relative to other types of eruptive activity such as Strombolian and Vulcanian, acoustic records of basaltic fissure eruptions with Hawaiian-style lava fountains are rare with previous studies limited to events at Etna (Cannata et al, 2009(Cannata et al, , 2011 and Kīlauea volcanoes (Fee et al, 2011;Lyons et al, 2021;Gestrich et al, 2021). Acoustic activity during these events are usually manifested as semi-continuous tremor with broadband frequency spectra characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Relative to other types of eruptive activity such as Strombolian and Vulcanian, acoustic records of basaltic fissure eruptions with Hawaiian-style lava fountains are rare with previous studies limited to events at Etna (Cannata et al, 2009(Cannata et al, , 2011 and Kīlauea volcanoes (Fee et al, 2011;Lyons et al, 2021;Gestrich et al, 2021). Acoustic activity during these events are usually manifested as semi-continuous tremor with broadband frequency spectra characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Jet noise frequency spectra exhibit self-similarity, with spectral shape remaining relatively constant and scaling with frequency, diameter, and velocity (Tam, 1998). Studies have shown that this self-similarity can extend to volcanic length scales (metres to hundreds of metres), therefore, similar relationships may exist between volcanic jet noise spectra and vent diameter, jet velocity, and temperature (Matoza et al, 2009(Matoza et al, , 2013McKee et al, 2017;Gestrich et al, 2021). While the spectral shapes are similar, the peak frequencies at volcanoes are generally lower and can be explained through the Strouhal number, a non-dimensional parameter used to describe oscillating flow (Seiner, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations